(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
Currently, personalized implants are becoming increasingly interesting topic, with additive manufacturing being one of the most effective solutions. Numerous research papers focus on enhancing mechanical properties while maintaining biocompatibility. A frequently utilized polymer in implant printing is polyethylene glycol diacrylate (PEGDA), which is additionally employed as a scaffold for antibiotics to prevent oral consumption and reduce the negative side effects of antibiotics on the human body. One of the most common photoinitiators used to polymerize the PEGDA is trimethylbenzoyl diphenylphosphine oxide (TPO), which is hazardous. This study aims to explore a technique for the selective removal of TPO from an implant to reduce the potential hazard, ensuring that the antibiotic remains intact. Two solvents were utilized: saline and a 96% ethanol solution. Consequently, ethanol demonstrated improved extraction efficiency of TPO from the polymer matrix, while maintaining the antibiotic content. This demonstrates that the TPO can be selectively extracted from the implant, thereby minimizing potential risks.